Analisis Pengaruh Kredibilitas Endorser Terhadap Minat Beli Dengan Kredibilitas Merek Sebagai Variabel Intervening (Studi Pada Produk smartphone Vivo Di Kota Semarang) - Veka Nanda Homer; Augusty Tae Ferdinand (Diponegoro Journal of Management, 2023)
ABSTRACT Abstract. Developments that occur in the current digital era encourage various companies or entrepreneurs to set the right marketing strategy for the products or services to be marketed. Through the services of endorsers as a marketing strategy made by companies or entrepreneurs to better introduce brands or brands to the public. In this study tested the expertise, trust, attractiveness, to purchase intention with brand credibility as intervening variables. The research begins with the development of a framework that analyzes the relationship between endorser credibility, brand credibility, and purchase intention based on Self Congruence Theory. The population in this study are people who live in the city of Semarang who know or buy Vivo smartphone products. Data collection involved 150 respondents with a questionnaire method selected by purposive sampling. The data obtained from the questionnaire data were then analyzed quantitatively and using the Structural Equation Modeling (SEM) method using a tool in the form of the Analysis Moment Of Structural (AMOS) version 24 program. The results of this study show that expertise, trustworthiness, attractiveness, which promote Vivo smartphone products have a positive and significant effect on brand credibility. Furthermore, brand credibility also has a positive influence on purchase intention. Therefore all hypotensives in this study are accepted and it is hoped that the managerial implications of this study can be suggestions for improvements to the VIVO Smartphone.